Pengaruh Profitabilitas Dan Kebijakan Dividen Terhadap Harga Saham Indeks Lq 45 Bursa Efek Indonesia - Yulia Pebrianti (JURNAL RISET TERAPAN AKUNTANSI, 2020)
This research is aimed to test the correlation of profitability ratio such as return on asset (ROA); return on equity (ROE); earning per share (EPS); and dividend policy such as dividend payout ratio (DPR); and yield on stock price. The research uses a data set consist of 45 companies listed as LQ-45 Index in 2017 period. Purposive sampling is used as sampling method. Regression analysis is used to compute the parameters. The results show that ROA has no significant correlation with stock price; ROE has significant correlation with stock price; EPS has significant correlation with stock price; DPR has no significant correlation with stock price; and Yield has no significant correlation with stock price. Key words: ROA, ROE, EPS, DPR, Yield, Stock Price.